New system design for the cultivation of extractive species at exposed sites - Part 1: System design, deployment and first response to high-energy environments ... - Heasman, Kevin G.; Scott, Nicholas; Smeaton, Malcolm; Goseberg, Nils; Hildebrandt, Arndt; Vitasovich, Peter; Elliot, Andrew; Mandeno, Michael; Buck, Bela H. (Amsterdam [u.a.] : Elsevier Science, 2021)
The purpose of this publication is to perform a system analysis of new cultivation technology for exposed bivalve farming. The technical feasibility of the new construction, called Shellfish Tower, was assessed. The device has gone through several very different phases of development on its way to the deployment of the prototype. These included multiple iterations during the designing stage, wave tank testing, fabrication, loading and unloading on trucks and vessels, deployment at sea, installation and assembly on the single mooring line, and bring it to its final position in a submerged mode 5m-10 m below the water surface. The final structure has a hexagonal body, with a centrally orientated variable buoyancy unit with culture sub-units on each of the six corners. These sub-units can be used for the culture of oysters (Magallana gigas – formally Crassostrea gigas) as well as for the collection of mussel spat (Perna canaliculus). Other possible candidates could be seaweed, lobsters, sponges or tunicates. ...